Managing subjectivity and the dialectic of self-consciousness: Hegal and organization theory - Hancock, Philip; Tyler, Melissa (2001)
This article presents the work and ideas of the German philosopher G.W.F. Hegel as a means of addressing recent debates concerning the management of employee subjectivity within contemporary work organizations. Drawing primarily upon his writings on the phenomenological development of `self-consciousness' and the concept of `ethical life' as a state of realized subjectivity, the authors argue that they provide a meta-theoretical framework within which the processual ontology of organizational (inter) subjectivity can be both addressed and critically appraised. This is then illustrated by a discussion of the role corporate culturalism plays in the mediation of this process, with particular attention being paid to its impact on the embodied dimension of the subject. - Reproduced.
Keywords: Hegel, G.W.F.; Organizations